Scrutinizing the 'feminization of agriculture' hypothesis: trajectories of labour force participation in agriculture in Indonesia - Juniwaty, Kartika (Center for International Forestry Research, 2019)
Presented by Kartika Juniwaty (Center for International Forestry Research), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.